Karakteristik Marshall Campuran AC-BC Menggunakan 4% Getah Damar Sebagai Pengganti Aspal - Kusmira Agustian; Roni Agusmaniza (Siklus : Jurnal Teknik Sipil, 2022)
Efforts to improve the quality of asphalt mixture can be done by modifying the asphalt. Materials that can be used to modify asphalt include plastic waste, waste tires, rubber latex, and gum resin. In this research, the modified material used is gum resin at 4% of the weight of the asphalt in the mixture as a substitute material. This research aims to determine the impact of using gum resin on the asphalt concrete-binder course (AC-BC) mixture on Marshall parameters. The method used is by conducting experiments in the laboratory starting with the search for the optimum asphalt content (OAC) either using gum resin or not as a comparison asphalt mixture. After obtaining the KAO values ​​from the two types of mixtures, the next step is to make samples using 4% gum resin on OAC to be compared with samples of asphalt mixture in OAC without using gum resin.. Research results show that the use of asphalt-modified material in the form of gum resin powder has been able to achieve the value of the Marshall parameter requirements set. A substantial difference in this research is in the stability value, where the asphalt mixture using gum resin is obtained at 2380.48 kg, while the asphalt mixture without gum resin is obtained at 2143.92 kg. The durability value of the mixture using gum resin was obtained at 96.88%, and the durability value of the mixture without gum resin was obtained at 97.02%. It shows that the use of gum resin as a modified asphalt material can produce a mixture of asphalt that is stronger in accepting vehicle wheel loads and can withstand changes in temperature and weather as indicated by the results of a durability value greater than 90%.